2003
DOI: 10.1152/japplphysiol.00411.2002
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic autonomic nervous effects on cell migration to the spleen

Abstract: This work is based on the hypothesis that sympathetic nerves regulate the uptake of circulating cells by the spleen by affecting splenic blood flow and that the quantity of cells sequestered depends on whether changes in noradrenergic transmission occur at local or systemic levels. Fluorescently labeled lymphoid cells were injected into rats, and organ blood flow was measured by the microsphere method. Increased retention of cells in the spleen paralleled by increased blood flow was detected after local denerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…In view of the historical role of acetylcholine as a potent vasodilator, and the relatively abundant cholinergic innervation to blood vessels seen in the current study, acetylcholine (and perhaps vagus nerve stimulation) may modulate immunity via local or systemic hemo- and lymphodynamic changes. In the past, studies have shown that autonomic nerves influence splenic immunity via blood flow (Reilly, 1985; Rogausch et al, 2003). In addition to modulating blood and lymph flow, it has been proposed that autonomic neurons endings in the spleen can directly modulate immune cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the historical role of acetylcholine as a potent vasodilator, and the relatively abundant cholinergic innervation to blood vessels seen in the current study, acetylcholine (and perhaps vagus nerve stimulation) may modulate immunity via local or systemic hemo- and lymphodynamic changes. In the past, studies have shown that autonomic nerves influence splenic immunity via blood flow (Reilly, 1985; Rogausch et al, 2003). In addition to modulating blood and lymph flow, it has been proposed that autonomic neurons endings in the spleen can directly modulate immune cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…The pulsating vessels, which may be the arteriolar capillaries that were reported in human spleen, control the flow of blood into the white pulp nodules and may be responsible for these hotspots (10). In fact, a recent report showed that blood flow to the rat spleen could be greatly increased by denervation of the organ, suggesting the existence of a mechanism for control of blood flow in the spleen (35). It is quite feasible that the autonomic nervous system controls these pulsating vessels allowing for rapid changes in blood flow through the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated recently that stimulation with either epinephrine or norepinephrine induced an increased accumulation of lymphocytes in spleen and lymph nodes 1-2 hours after injection with a complex re-distribution pattern from the splenic red to the white pulp and to the pericortex of lymph nodes [49]. In line with this, it was proposed that the spleen may be the main source for the observed adrenergic cell mobilization, but studies in splenectomized volunteers revealed that in these subjects, cells were mobilized from other sources, for example the marginal pool [21,47,[49][50][51][52][53].…”
Section: The Immunomodulatory Effect Of Peripheral Circulating Catechmentioning
confidence: 99%